Efficacy and safety of probiotics as a complementary treatment for urticaria: a systematic review and meta-analysis - Tan, Danni; Liao, Ke; Yu, Yunfeng; Yin, Yuman; Qin, Lina; Xiang, Qin; Yu, Rong (Frontiers in Microbiology, 2025)
ObjectiveThe potential of probiotics in the treatment of urticaria has garnered significant attention. However, a systematic assessment of their benefits and risks is lacking. This meta-analysis and trial sequential analysis (TSA) aim to evaluate the efficacy and safety of probiotics as a complementary treatment for urticaria.MethodsRelevant studies published before April 30, 2025, were retrieved and screened from eight public databases. The basic characteristics, outcome data, and risk of bias of the included studies were recorded. Meta-analysis and TSA were conducted using Review Manager 5.3 and TSA 0.9.5.10 Beta, respectively. Funnel plots and Egger’s test were employed to assess publication bias, while the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system was used to evaluate the certainty of evidence.ResultsA total of 11 clinical trials involving 1,014 participants were included in this study. The meta-analysis revealed that, compared to antihistamines alone, the combination of probiotics and antihistamines significantly improved the urticaria relief rate (URR) (odds ratio [OR] 2.90, 95% confidence interval [CI] 1.97 to 4.28, p < 0.00001) and interferon-gamma (IFN-γ) levels (mean difference [MD] 8.12, 95% CI 6.95 to 9.30, p < 0.00001). Additionally, it reduced the urticaria activity score over 7 days (UAS7) (MD −3.29, 95% CI −3.28 to −2.75, p < 0.00001), the dermatology life quality index (DLQI) (MD −2.95, 95% CI −3.21 to −2.69, p < 0.00001), interleukin-10 (IL-10) levels (MD −1.47, 95% CI −2.01 to −0.93, p < 0.00001), adverse event rate (AER) (OR 0.39, 95% CI 0.20 to 0.77, p = 0.007), and recurrence rate (OR 0.29, 95% CI 0.14 to 0.60, p = 0.0008). The TSA confirmed the conclusiveness of the aforementioned meta-analysis results. Egger’s test indicated no significant publication bias for these outcomes.ConclusionProbiotics not only improve clinical symptoms in patients with urticaria but may also reduce the incidence of adverse events and recurrence rates. This highlights the potential of probiotics as a complementary treatment for urticaria. However, due to the risk of bias in the existing studies, these findings need to be validated through high-quality clinical trials.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251232590, CRD420251232590.